Stage-Wise Learning of Reaching Using Little Prior Knowledge - de La Bourdonnaye, François; Teulière, Céline; Triesch, Jochen; Chateau, Thierry (Frontiers in Robotics and AI, 2018)
In some manipulation robotics environments, because of the difficulty of precisely modelling dynamics and computing features which describe well the variety of scene appearances, hand-programming a robot behaviour is often intractable. Deep reinforcement learning methods partially alleviate this problem in that they can dispense with hand-crafted features for the state representation and do not need pre-computed dynamics. However, they often use prior information in the task definition in the form of shaping rewards which guide the robot towards goal state areas but require engineering or human supervision and can lead to sub-optimal behaviour. In this work we consider a complex robot reaching task with a large range of initial object positions and initial arm position and propose a new learning approach with minimal supervision. Inspired by developmental robotics, our method consists of a weakly-supervised stage-wise procedure of three tasks. First, the robot learns to fixate the object with a 2-camera system. Second, it learns hand-eye coordination by learning to fixate its end-effector. Third, using the knowledge acquired in the previous steps, it learns to reach the object at different positions and from a large set of initial robot joint angles. Experiments in a simulated environment show that our stage-wise framework yields similar reaching performances, compared with a supervised setting without using kinematic models, hand-crafted features, calibration parameters or supervised visual modules.